«Truth is an odd number». La narrativa di Flann O'Brien e il fantastico - Milli, Valentina (Biblioteca di Studi di Filologia Moderna, 2014)
Starting from the main theories about the imaginary - from the Freudian category of Unheimliche and the Todorovian category of hésitation up to the most recent contributions - the volume highlights the imaginary elements of instability in Flann O'Brien's narrative. In particular, the author analyses the discontinuities and irreconcilable contradictions of the Irish writer's textual systems, the idiosyncratic and fragmented representation of the characters, the ambiguous coexistence of natural and supernatural, the problematic relationship between signifier and signified. Malapropisms, neologisms, linguistic tics, nonsense and a series of meta-narrative games seem to compromise the search for reliable answers within the Obrienian cosmos in which truth is, in fact, an odd number.